A 2-hydroxybutyrate-mediated feedback loop regulates muscular fatigue - Brennan J Wadsworth; Marina Leiwe; Eleanor A Minogue; Pedro P Cunha; Viktor Engman; Carolin Brombach; Christos Asvestis; Shiv K Sah-Teli; Emilia Marklund; Peppi Koivunen; Jorge L Ruas; Helene Rundqvist; et al. (eLife, 2024)
Several metabolites have been shown to have independent and at times unexpected biological effects outside of their metabolic pathways. These include succinate, lactate, fumarate, and 2-hydroxyglutarate. 2-Hydroxybutyrate (2HB) is a byproduct of endogenous cysteine synthesis, produced during periods of cellular stress. 2HB rises acutely after exercise; it also rises during infection and is also chronically increased in a number of metabolic disorders. We show here that 2HB inhibits branched-chain aminotransferase enzymes, which in turn triggers a SIRT4-dependent shift in the compartmental abundance of protein ADP-ribosylation. The 2HB-induced decrease in nuclear protein ADP-ribosylation leads to a C/EBPβ-mediated transcriptional response in the branched-chain amino acid degradation pathway. This response to 2HB exposure leads to an improved oxidative capacity in vitro. We found that repeated injection with 2HB can replicate the improvement to oxidative capacity that occurs following exercise training. Together, we show that 2-HB regulates fundamental aspects of skeletal muscle metabolism.